2023
DOI: 10.1002/adhm.202203177
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Carrier‐Free Nanodrugs for Starvation Therapy‐Amplified Photodynamic Therapy of Cancer

Abstract: Traditional starvation treatment strategies, which involve glucose oxidase and drug‐induced thrombi, often suffer from aggravated tumor hypoxia and have failed to improve antitumor efficacy in combination with oxygen‐dependent photodynamic therapy (PDT). Herein, glucose transporter 1 inhibitor genistein (Gen) and photosensitizer chlorin e6 (Ce6) are integrated to construct carrier‐free self‐assembled nanoparticles defined as GC NPs, for starvation therapy‐amplified PDT of tumor. GC NPs with regular morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The d17–Ce6 NPs were stable in pure water and 1640 containing 10% FBS, and the particle size did not change significantly within 7 days (Figure H). In addition, the zeta potential of d17–Ce6 NPs was roughly −33 mV, which could inhibit their interaction with proteins in the blood . Furthermore, the polydispersity index (PDI) of d17–Ce6 NPs in the aqueous solution have showed negligible change (Figure I), which suggested the agreeable dispersity and steadiness of the prepared d17–Ce6 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The d17–Ce6 NPs were stable in pure water and 1640 containing 10% FBS, and the particle size did not change significantly within 7 days (Figure H). In addition, the zeta potential of d17–Ce6 NPs was roughly −33 mV, which could inhibit their interaction with proteins in the blood . Furthermore, the polydispersity index (PDI) of d17–Ce6 NPs in the aqueous solution have showed negligible change (Figure I), which suggested the agreeable dispersity and steadiness of the prepared d17–Ce6 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…NaCl, urea, and Sodium dodecyl sulfate (SDS) were used as inhibitors of electrostatic interactions, intermolecular hydrogen bonding, and hydrophobic effects, respectively, with H 2 O serving as a comparison. [49] NaCl dissociates into Na + and Cl-in solution, which can form ion pairs with charged molecules and reduce the interaction forces between charged molecules. Urea can form hydrogen bonds with water molecules, preventing the formation of hydrogen bonds between large molecules and water molecules.…”
Section: The Drug Loading and Releasing Behavior Under Different Cond...mentioning
confidence: 99%
“…The results indicated that GC showed an excellent antitumor effect. 144 Table 6 lists various combination phototherapies with ST for tumor treatment. These therapies have been demonstrated to improve anticancer effects compared with phototherapy or ST alone.…”
Section: Combination Of Phototherapy and Starvation Therapymentioning
confidence: 99%